Effects of various feeding patterns of Bacillus coagulans on growth performance, antioxidant response and Nrf2-Keap1 signaling pathway in juvenile gibel carp (Carassius auratus gibelio). Issue 73 (February 2018) - Yu, Yebing; Wang, Changhai; Wang, Aimin; Yang, Wenping; Lv, Fu; Liu, Fei; Liu, Bo; Sun, Cunxin
Abstract: The present study was conducted to evaluate the effects of various Bacillus coagulans feeding patterns on growth, antioxidant parameter and Nrf2 pathway in juvenile gibel carp. The similar size of gibel carp (initial weight: 14.33 ± 0.15 g) were subjected to three levels of B. coagulans supplementation (0, 500, and 1000 mg/kg) and two feeding modes (supplementing B. coagulans continuously or for two days of B. coagulans after 5 days of a basal diet) according to a 3 × 2 factorial design. The fish that were continuously fed 500 mg/kg B. coagulans (P2) and those fed the first basal diet for 5 days followed by 500 mg/kg or 1000 mg/kg B.coagulans for 2 days (P4 or P5) showed higher weight gain rate and specific growth rate than the other groups. Blood respiratory burst (RB), myeloperoxidase (MPO), and anti-superoxide anion free radical (AFASER) activities in the P4 group were higher than those of the control. White blood cell count (WBC), RB activity, MPO activity, and glutathione (GSH) content in the P5 group were also higher than those of the control. A similar higher trend was observed in the gene expressions of NADPH oxidase 2 (NOX2), NFE2-related factor (Nrf2), Kelch-like-ECH-associated protein(Keap1) in the P4 and NOX2, NRF2, CNC homolog 1 (Bach1), peroxiredoxin 2 (Prx2) in the P5 group compared with the control. Additionally, we observed a significantly lower level of plasma aspartate aminotransferase (AST), lower activity of alanine aminotransferase (ALT), a higher level of MPO, higher GPX activity, and increased NRF2 and Prx2 expression were all observed in the P2 treatment group compared with the control. Furthermore, the malondialdehyde (MDA) content in the P2, P3, and P4 groups was lower than that of the control. These results indicate that a diet supplemented with appropriate levels of B.coagulans could improve the growth, immune response, and antioxidant capability of gibel carp. We concluded that the pattern of two days of 500 or 1000 mg/kg B. coagulans after 5 days of a basal diet was recommended for gibel carp. Highlights: The feeding strategies of Bacillus coagulans impacted on the growth performance of gibel carp. Dietary Bacillus coagulans activated Nrf2-Keap1 pathway of antioxidant gene regulation. The feeding strategies of Bacillus coagulans prevented the damage of oxidative stress.